2023
DOI: 10.55730/1300-0144.5615
|View full text |Cite
|
Sign up to set email alerts
|

Screening of antigliadin and antitissue transglutaminase antibodies in patients with chronic plaque psoriasis: a case-control study

Abstract: Background/aim In this study, we aimed to investigate different types of celiac antibodies in psoriasis patients and to see if the presence of the antibodies was associated with other variables. Materials and methods We included patients with plaque psoriasis who were followed up in our dermatology clinic between February 2019 and February 2021 and added a healthy control group for comparison. The antibodies studied were serum antitissue transglutaminase (tTG)-IgA, tTG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Histone modification has been shown to interact with the immune microenvironment and promote the occurrence and development of inflammatory skin diseases. A study reported that the α-KG–H3K9me3–BBOX1 axis is critical in the metabolic reprogramming of cluster of differentiation (CD)147, which is pivotal in glycolysis reprogramming during the pathogenesis of psoriasis ( 25 ). One of the histone deacetylases, SIRT1, potentially inhibits the apoptosis of keratinocytes induced by UVB in cutaneous lupus erythematosus ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Histone modification has been shown to interact with the immune microenvironment and promote the occurrence and development of inflammatory skin diseases. A study reported that the α-KG–H3K9me3–BBOX1 axis is critical in the metabolic reprogramming of cluster of differentiation (CD)147, which is pivotal in glycolysis reprogramming during the pathogenesis of psoriasis ( 25 ). One of the histone deacetylases, SIRT1, potentially inhibits the apoptosis of keratinocytes induced by UVB in cutaneous lupus erythematosus ( 26 ).…”
Section: Introductionmentioning
confidence: 99%